A Critical Evaluation of the Methodological Obstacles to Translating Cell-Based Research Into an Effective Treatment for People With Parkinson's Disease. (October 2016) - Polgar, Stephen; Karimi, Leila; Buultjens, Melissa; Morris, Meg E.
The remarkable scientific and technological advances in the field of cell research have not been translated into viable restorative therapies for brain disorders. In this article, we examine the best available evidence for the clinical efficacy of reconstructive intracerebral transplantation in people with Parkinson's disease (PD), with the aim of identifying methodological obstacles to the translation process. The major stumbling block is the fact that the potential contributions of people with neural grafts and the effects of the physical and social environment in which they recover have not been adequately investigated and applied to advancing the clinical stages of the research program. We suggest that the biopsychosocial model along with emerging evidence of targeted rehabilitation can provide a useful framework for conducting research and evaluation that will ensure the best possible outcomes following intracerebral transplantation for PD.